(untitled) (SciELO Preprints, 2026)
Semantics plays a central role in the development of reading and writing skills, as it directly engages the human capacity to construct, negotiate, and interpret meaning. Accordingly, educational systems should systematically foster students’ interpretive and expressive competences throughout Basic Education. Despite its relevance, however, the study of meaning remains largely absent from curricular guidelines and pedagogical practices, often appearing only in fragmented discussions of lexical relations. This gap may stem from the absence of a clearly articulated framework capable of defining what semantic knowledge should be explicitly taught in schools. This study addresses this issue by proposing a conceptual foundation for semantics instruction grounded in Pilati (2017, 2021). It builds on the assumption that effective pedagogical practice depends on a coherent theoretical framework capable of systematizing linguistic reasoning and, consequently, enhancing students’ proficiency in linguistic analysis, reading, and text production (Pilati, 2021). More specifically, the paper argues that semantic awareness should be developed through the explicit understanding of three core domains of semantic knowledge, organized in increasing levels of complexity: signification, which concerns the relationship between language and reference; categorization, which involves the attribution of properties and predication; and referentiation, which concerns the introduction, maintenance, and tracking of referents throughout textual construction.